Public and Hidden Economies in Atuntaqui (Ecuador): The Challenge of Sustaining Cooperation in Textile Production - Colloredo-Mansfeld, Rudi (2013)
In the 2000s, Atuntaqui’s quality improvement program, joint marketing investments, and cultural initatives were designed to leverage the power of strategic cooperation. Over the course of several development projects, however, social interactions became more inclusive and more contentious. In this paper, we introduce the idea of a public economy and contrast it with narrower social capital theories to account for the benefits of Atuntaqui’s move from hidden production to an open trade. With data from field research that spans seven years, this article documents how the pressures of rapid manufacturing growth and the missteps in managing civic projects have undermined public participation and closed off important features of the public economy. The paper concludes with observation about how to revive more robust collaborations through diversification of local participants, strengthening of the chamber of commerce, and recognizing and including the large wave of new, smaller producers.